Effect of gallbladder hypomotility on cholesterol crystallization and growth in CCK-deficient mice - Wang, Helen H. (2009)
We investigated the effect of gallbladder hypomotility on cholesterol crystallization and growth during the early stage of gallstone formation in CCK knockout mice. Contrary to wild-type mice, fasting gallbladder volumes were enlarged and the response of gallbladder emptying to a high fat meal was impaired in knockout mice on chow or the lithogenic diet. In the lithogenic state, large amounts of mucin gel and liquid crystals as well as arc-like and tubular crystals formed first, followed by rapid formation of classic parallelogram-shaped cholesterol monohydrate crystals in knockout mice. Furthermore, three patterns of crystal growth habits were observed: proportional enlargement, spiral dislocation growth, and twin crystal growth, all enlarging solid cholesterol crystals. At day 15 on the lithogenic diet, 75% of knockout mice formed gallstones. However, wildtype mice formed very little mucin gel, liquid and solid crystals, and gallstones were not observed. We conclude that lack of CCK induces gallbladder hypomotility that prolongs the residence time of excess cholesterol in the gallbladder, leading to rapid crystallization and precipitation of solid cholesterol crystals. Moreover, during the early stage of gallstone formation, there are two pathways of liquid and polymorph anhydrous crystals evolving to monohydrate crystals and three modes for cholesterol crystal growth.